2017
DOI: 10.1111/apt.14165
|View full text |Cite
|
Sign up to set email alerts
|

Letter: bias in clinical trials of the symptomatic effects of the low FODMAP diet for irritable bowel syndrome—getting the facts right. Authors' reply

Abstract: 3. Ong DK, Mitchell SB, Barrett JS, et al. Manipulation of dietary short chain carbohydrates alters the pattern of gas production and genesis of symptoms in irritable bowel syndrome. J Gastroenterol Hepatol. 2010;25:1366-1373 4. Zanini B, Basch e R, Ferraresi A, et al. Randomised clinical study: gluten challenge induces symptom recurrence in only a minority of patients who meet clinical criteria for non-coeliac gluten sensitivity. Ong et al., 4 reported that patients with irritable bowel syndrome (IBS) had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Krogsgaard et al noted that participants on the control diet had a significant difference in the visual analogue scale (VAS) compared with the baseline diet (VAS 44.9 vs 36.0, p<0.001). It was suggested that this may have been attributed to the higher FODMAP content of the control diet versus the baseline diet, which may have led to favourable benefits of the low FODMAP diet seen in the study[27].There have been several Randomized Controlled Trials (RCTs) published demonstrating the benefits of a low FODMAP diet in IBS, with Table I outlining some of these…”
mentioning
confidence: 99%
“…Krogsgaard et al noted that participants on the control diet had a significant difference in the visual analogue scale (VAS) compared with the baseline diet (VAS 44.9 vs 36.0, p<0.001). It was suggested that this may have been attributed to the higher FODMAP content of the control diet versus the baseline diet, which may have led to favourable benefits of the low FODMAP diet seen in the study[27].There have been several Randomized Controlled Trials (RCTs) published demonstrating the benefits of a low FODMAP diet in IBS, with Table I outlining some of these…”
mentioning
confidence: 99%